Institutional review boards in Saudi Arabia: the first survey-based report on their functions and operations - AlFattani, Areej; AlBedah, Norah; AlShahrani, Asma; Alkawi, Ammar; AlMeharish, Amani; Altwaijri, Yasmin; Omar, Abeer; AlKawi, M. Zuheir; Khogeer, Asim (BMC medical ethics, 2023)
Institutional review boards (IRBs) are formally designated to review, approve, and monitor biomedical research. They are responsible for ensuring that researchers comply with the ethical guidelines concerning human research participants. Given that IRBs might face different obstacles that cause delays in their processes or conflicts with investigators, this study aims to report the functions, roles, resources, and review process of IRBs in Saudi Arabia. This was a cross-sectional self-reported survey conducted from March 2021 to March 2022. The survey was sent to 53 IRB chairpersons and the administration directors (or secretary) across the country through email after receiving verbal consent. The validated survey consisted of eight aspects: (a) organizational aspects, (b) membership and educational training, (c) submission arrangements and materials, (d) minutes, (e) review procedures, (f) communicating a decision, (g) continuing review, and (h) research ethics committee (REC) resources. A total of 200 points indicated optimal IRB functions. Twenty-six IRBs across Saudi Arabia responded to the survey. Overall, the IRBs in this study scored a total of 150/200 of the points on the self-assessment tool. Relatively newer IRBs (established less than ten years ago) conducted meetings at least once in a month, had annual funding, had more balanced gender representation, tended to score higher than older IRBs. The organizational aspect score was the lowest among all items in the survey (14.3 score difference, p-value < 0.01). The average turnaround time for expedited research from proposal submission to final decision was 7 days, while it was 20.5 days for the full committee review. Saudi IRBs performed generally well. However, there is room for focused improvement with respect to extra resources and organizational issues that require closer evaluation and guidance from the regulatory bodies.